Millenium cities: dispossession and biopolitics in the Ecuadorian Amazon region - Aulestia Calero, Martín (2018)
This article investigates the “millennium cities” as a social and spatial phenomenon produced under Rafael Correa’s presidency. This phenomenon is discussed through three main viewpoints: concerning the capitalist production of the space, the specific strategy to make possible the processes of accumulation by dispossession in the Amazon, and a properly biopolitical strategy. In this way, millennium cities must be thought of as one of the local ways in which the universalization of the urban phenomenon adopts at a global scale from the necessities of capitalism, which finds in the production of space open channels for the execution of surplus and the revitalization of accumulation. Millennium cities can be thought of as a specifically biopolitical strategy that pretends to manage the life of native communities in order to make possible the devices needed for accomplishing accumulation by dispossession. The millennium cities aim to homogenize the forms of living and the concrete, temporal and spatial experiences, all of which allows is a testimony of how president Correa’s government denies indigenous communities their role as legitimate interlocutors and political actors, while at the same time asserts the sovereign intention of the Ecuadorian national state.